Effect of Dike Width on Pore Pressure and Water Content Evolution During Overtopping Conditions - Hassan, Marwan A.; Shaalan, Heyam H.; Al-Deewan, Hayder A. O. (Salehan Institute of Higher Education, 2026)
The failure of dike embankments due to overtopping flow plays a crucial role in understanding the mechanisms behind dike erosion, which is essential for effective disaster mitigation. The